Prognostic Influence of Preoperative Fibrinogen to Albumin Ratio for Breast Cancer - Ki‐Tae Hwang; Jung Kee Chung; Eun Youn Roh; Jong-Jin Kim; Sohee Oh; Young A Kim; Jiyoung Rhu; Suzy Kim (2017)
Elevated serum concentration of fibrinogen and decreased serum concentration of albumin have been reported to be markers of elevated systemic inflammation. We attempted to investigate the prognostic influence of preoperative fibrinogen to albumin ratio (FAR) for breast cancer.Data from 793 consecutive primary breast cancer patients were retrospectively analyzed. Serum levels of fibrinogen and albumin were tested before curative surgery. Subjects were grouped into two groups according to the cutoff value determined by performing the receiver operating characteristic curve analysis: the high FAR group (FAR>7.1) and the low FAR group (FAR≤7.1). Overall survival was assessed using the Kaplan-Meier estimator. Independent prognostic significance was analyzed using the Cox proportional hazards model.The high FAR group had a worse prognosis compared to the low FAR group (log-rank test, p<0.001). The prognostic effect of FAR was more significant than that of single markers such as fibrinogen (log-rank test, p=0.001) or albumin (log-rank test, p=0.001). The prognostic effect of FAR was prominent in the stage II/III subgroup (log-rank test, p<0.001) and luminal A-like subtype (log-rank test, p<0.001). FAR was identified as a significant independent factor on both univariate (hazard ratio [HR], 2.722; 95% confidence interval [CI], 1.659-4.468; p<0.001) and multivariate analysis (HR, 2.622; 95% CI, 1.455-4.724; p=0.001).Preoperative FAR was a strong independent prognostic factor in breast cancer. Its prognostic effect was more prominent in the stage II/III subgroup and in the luminal A-like subtype. Therefore, preoperative FAR can be utilized as a useful prognosticator for breast cancer patients. Further studies are needed to validate its applications in clinical settings.